Фінансова безпека банківських установ в умовах цифровізації - Теслюк, Софія Анатоліївна; Матвійчук, Наталія Миколаївна; Левчук, Анастасія Олегівна (Видавничий дім "Гельветика", 2024)
У статті досліджено вплив цифровізації на фінансову безпеку банківських установ. Визначено, що в економічній літературі безпека банку розглядається як комплекс заходів для захисту інтересів власників, клієнтів, працівників і керівництва банку від зовнішніх і внутрішніх загроз, що є ключовим елементом банківського менеджменту. Розглянуто індикатори фінансової безпеки банківської діяльності під впливом цифровізації. Проаналізовано основні прояви інноваційної діяльності банківської установи. Перераховано банків-лідерів, які впроваджують різні види інноваційних технологій. Визначено основні загрози функціонування банківських інновацій та перспективи їх розвитку на основі зарубіжного досвіду. Запропоновано ряд заходів які допоможуть покращити функціонування новітніх технологій у банках в контексті забезпечення їх фінансової безпеки.

The purpose of the article is to study the essence of the concept of financial security of banking institutions, to identify threats to their financial security in the conditions of digitalization, as well as to establish directions for their neutralization and overcoming. In connection with the rapid development of digital technologies, the financial security of banking institutions is becoming an increasingly urgent and complex problem. It was determined that in economic literature, bank security is considered as a set of measures to protect the interests of owners, customers, employees and management of the bank from external and internal threats, which is a key element of bank management. The indicators of the financial security of banking under the influence of digitalization are considered, which include: the prevalence of Internet banking and mobile banking, the existence of a network of ATMs and POS terminals in the bank, means of centralized detection of illegal attempts to penetrate the resources of the banking system, the use of artificial intelligence technologies, the use of databases in the banking sector, based on the «client-server» model, etc. Threats to the bank's financial security have been classified. The main manifestations of the innovative activity of the banking institution were considered in the study, among which the digitization of back-office operations, electronic payment technologies, cloud technologies, the use of chatbots based on artificial intelligence, P2P (PeertoPeer) lending, biometric methods of identification, use Bank ID, internet banking, QR-banking, blockchain. Leading banks implementing various types of innovative technologies are listed. The main threats to the functioning of banking innovations and prospects for their development based on foreign experience are determined. A number of measures are proposed that will help improve the functioning of the latest technologies in banks in the context of ensuring financial security. Thus, banking innovations not only strengthen financial security, but also contribute to the sustainable development of the banking system, responding to the challenges of the modern financial environment. They are a key tool for ensuring the financial security of a banking institution, allowing it to effectively face the challenges and risks of the modern financial environment
Keywords: банківські установи; banks; фінансова безпека; financial security; банківські інновації; banking innovations; цифровізація; digitalization; банківські продукти і послуги; banking products and services; індикатори фінансової безпеки; indicators of financial security; G 21; 336.71:336.1-049.5]:004.9